The extent and mechanism of the effect of protectant material in the production of active lactic acid bacteria powder using spray drying: a review. (April 2022) - Wang, Ni; Fu, Nan; Chen, Xiao Dong
Highlights: Survival of spray-dried LAB can be enhanced by modifying protective carriers. Carriers protect LAB from inactivation based on both external and internal effects. Carriers could lower the intensity of stresses exerting on LAB cells during drying. Assimilation or accumulation of carriers may change the stress tolerance of cells. Abstract : For the production of powders containing active lactic acid bacteria (LAB), spray drying offers a rapid and cost-effective approach with high production capacity, making it a promising alternative to the common freeze drying approach in industrial practice. Various strategies have been developed to counter the harsh conditions in the spray drying process and to increase the retention of LAB viability, based on multidisciplinary mechanisms related to microbiology, food chemistry, and drying. Protectant formulation is one of the most important factors affecting the survival of spray-dried LAB, for it impacts on both external and internal causes for the inactivation of bacterial cells. An overview is provided on the effects of different types of protective agents during spray drying, and possible mechanisms are discussed.